For how many positive integers n , does this inequality hold? ( n + 1 ) n ! > 2 n
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Can you not say that if n = 1 is false and n = 2 is true, can you not say that the rest of the values are also true, making it infinite, @Mohammed Imran ?
Nice induction probem.
Let use Induction to show the above inequality holds true for all positive integers n ≥ 2 . If we rewrite it as n ! > ( n + 1 ) 2 4 n , then we have:
CASE I ( n = 2 ): 2 ! > ( 2 + 1 ) 2 4 2 ⇒ 2 > 9 1 6 ≈ 1 . 7 8 ⇒ (TRUE).
CASE II ( n = k ) : k ! > ( k + 1 ) 2 4 k ⇒ (ASSUMED TRUE).
CASE III ( n = k + 1 ) : ( k + 1 ) ⋅ k ! > ( k + 1 ) 2 4 k ⋅ ( k + 1 ) ;
or ( k + 1 ) ! > k + 1 4 k ⋅ 4 ( k + 2 ) 2 4 ( k + 2 ) 2 ;
or ( k + 1 ) ! > [ ( k + 1 ) + 1 ] 2 4 k + 1 ⋅ 4 ( k + 1 ) ( k + 2 ) 2 ;
or ( k + 1 ) ! > [ ( k + 1 ) + 1 ] 2 4 k + 1 ⋅ 4 ( k + 1 ) k 2 + 4 k + 4 ;
or ( k + 1 ) ! > [ ( k + 1 ) + 1 ] 2 4 k + 1 ⋅ [ 1 + 4 ( k + 1 ) k 2 ] > [ ( k + 1 ) + 1 ] 2 4 k + 1 ;
or ( k + 1 ) ! > [ ( k + 1 ) + 1 ] 2 4 k + 1 ⇒ (TRUE).
Q . E . D .
Problem Loading...
Note Loading...
Set Loading...
We will prove that it holds for all n ∈ N , n − 1 . Consider the expression ( 1 + 1 1 ) ( 1 + 2 1 ) . . . ( 1 + n 1 ) this expression is n + 1 . Also, ( 1 + 1 1 ) ( 1 + 2 1 ) . . . ( 1 + n 1 ) > ( 1 2 ) ( 2 2 ) . . . ( n 2 ) = n ! 2 n so, we can conclude that n + 1 > n ! 2 n ⟹ ( n + 1 ) n ! > 2 n